A HOLOCENE SEDIMENTARY RECORD FROM BOSTEN LAKE, CHINA - Wünnemann B.; Mischke S.; Chen F. (My University, 2006)
A 9.24 m long sediment record from the Kaidu River delta margin of Bosten Lake, northwestern China, provides evidence for changes in water balance of the lake during the past 8600 calendar years. Quantitative and qualitative analyses of detrital components, authigenic calcite, TOC and Sr/Ca molar ratios as well as comparisons with selected ostracod assemblages show that lake level fluctuations at minimum 5-6 m display changes in effective moisture supply, mainly driven by the west wind system. Distinct periods of negative water balances and thus dry conditions are dated to 8.5-8.1, 7.3-7.1, around 6.0, at 5.4-5.0, 4.6-4.3, 3.9-3.6, 3.4-3.2, 2.6-2.5, 1.9-1.1, 0.5-0.3 and 0.18-0.05 cal. ky BP and match the regional and global pattern of climate shifts during the Holocene. Temporal shifts of moisture availability during mid-Holocene time were recognised as well and may be attributed to regionally different airflow conditions. The last 150 years of rising lake levels are accompanied by strong eutrophication as a result of increased human impact. © 2005 Elsevier B.V. All rights reserved.
Keywords: BOSTEN LAKE; HOLOCENE; PALAEOCLIMATE; SEDIMENT RECORD; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен